2019
DOI: 10.1016/j.molmet.2019.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Imaging adipose tissue browning using the TSPO-18kDa tracer [18F]FEPPA

Abstract: Objectives The browning of white adipose tissue (WAT) into beige has been proposed as a strategy to enhance energy expenditure to combat the growing epidemic of obesity. Research into browning strategies are hampered by the lack of sensitive, translatable, imaging tools capable of detecting beige fat mass non-invasively. [ 18 F]FDG is able to detect activated beige fat but provides little information on unstimulated beige fat mass. We have assessed the use of [ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…In fact, many proteins, including TSPO (expressed on the outer mitochondrial membrane), are also potential targets of BAT imaging. In contrast, WAT shows less mitochondria number and TSPO expression than BAT (including unstimulated BAT and beige fat) [ 25 ]. Recent studies have confirmed that TSPO specific tracers, such as 11 C-PBR28 and [ 18 F]FEPPA, can be used for the imaging of BAT and to detect the browning of WAT [ 19 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, many proteins, including TSPO (expressed on the outer mitochondrial membrane), are also potential targets of BAT imaging. In contrast, WAT shows less mitochondria number and TSPO expression than BAT (including unstimulated BAT and beige fat) [ 25 ]. Recent studies have confirmed that TSPO specific tracers, such as 11 C-PBR28 and [ 18 F]FEPPA, can be used for the imaging of BAT and to detect the browning of WAT [ 19 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, WAT shows less mitochondria number and TSPO expression than BAT (including unstimulated BAT and beige fat) [ 25 ]. Recent studies have confirmed that TSPO specific tracers, such as 11 C-PBR28 and [ 18 F]FEPPA, can be used for the imaging of BAT and to detect the browning of WAT [ 19 , 25 ]. However, to the best of our knowledge, there is no published report about studying BAT activity with [ 18 F]DPA714, a mitochondrial TSPO-based imaging tracer.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, other groups have demonstrated the feasibility of TSPO PET tracers for BAT imaging. Goggi et al reported that 18 F-FEPPA was able to detect inguinal WAT browning but not BAT activation in mice after dosing with β3-adrenergic agonist CL-316,243 [60]. Their results indicated 18 F-FEPPA could be a promising tracer for BAT mass detection, independent of its metabolic state.…”
Section: Imaging Modalities For Bat Detection 21 Positron Emission Tomography (Pet)mentioning
confidence: 99%
“…The short (2 min) half-life of 15 O allows for repeat PET scanning with another tracer on the same day [77,79]. Investigational radiotracer currently include the mitochondrial outer membrane translocator protein, visualized with 18 F-FEPPA PET/CT and 11 C-PBR28 PET/CT, the cannabinoid type 1 receptor, visualized with 18 F-FMPEP-d2 PET/CT [80,81,82,83], and PD-L1, visualized with radiolabeled antibodies [84,85].…”
Section: Molecular Imaging With Radiotracersmentioning
confidence: 99%